2011
DOI: 10.1097/ico.0b013e31821379aa
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Subconjunctival and Intracorneal Bevacizumab Injection for Corneal Neovascularization

Abstract: Short-term results suggest that combined subconjunctival and intracorneal injections of bevacizumab are an effective method for reducing corneal neovascularization. It may be a useful option or adjunct to other treatments in stabilizing or improving vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 36 publications
2
24
0
2
Order By: Relevance
“…The results by Oh et al 37 showed profound regression of corneal NV by 60% after repeat injections, suggesting the cumulative effect of the drug and the effectiveness of intrastromal injection for deep corneal vessels. The study by Yeung et al, 26 which was not included in the meta-analysis as measurements of the corneal NV were not reported, showed similar results and effectiveness of the combination of topical and intrastromal administration in reducing corneal NV.…”
Section: Discussionsupporting
confidence: 61%
“…The results by Oh et al 37 showed profound regression of corneal NV by 60% after repeat injections, suggesting the cumulative effect of the drug and the effectiveness of intrastromal injection for deep corneal vessels. The study by Yeung et al, 26 which was not included in the meta-analysis as measurements of the corneal NV were not reported, showed similar results and effectiveness of the combination of topical and intrastromal administration in reducing corneal NV.…”
Section: Discussionsupporting
confidence: 61%
“…Prior studies showed that counteracting VEGF significantly reduces HSV-1-induced angiogenesis (Carrasco, 2008;Cook and Figg, 2010;M.E. Zheng et al, 2001;Yeung et al, 2011). VEGF stimulates EC to migrate and form new vessels, events needed for the development of vasculature and proposed as targets for antiangiogenic compounds (Cook and Figg, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…In noninfectious conditions such as BKC, corneal anesthesia, or exposure keratopathy, the mechanism of CN is poorly understood but is most likely related to weakness in the integrity and function of the blood vessel barrier provided by the limbal stem cells. 4 In adults, CN has been reported to respond to numerous treatment modalities including topical corticosteroids and nonsteroidal anti-inflammatory drops, 5 corneal argon laser photocoagulation, 6 photodynamic therapy, 7 fine needle diathermy (FND), 8,9 electrolysis-needle cauterization, 10 repeated bevacizumab injections (Avastin; Genentech, San Francisco, CA), 11 and ligation of blood vessel origin. 12 No treatment modality has been reported to be completely effective in eradicating blood vessels from the cornea and often, repeated treatments are required.…”
Section: Conclusion: Corneal Fnd With Adjuvant Bevacizumab Injectionmentioning
confidence: 99%